Anthropometry Versus Imaging for Prediction of Inflammation Among Hispanic Girls. Issue 10 (1st October 2018) - Bea, Jennifer W.; Funk, Janet; Hetherington‐Rauth, Megan; Wertheim, Betsy C.; Mosquiera, Lucia; Thuraisingam, Ravina; Lee, Vinson; Blew, Robert; Lohman, Timothy; Roe, Denise J.; Going, Scott
Abstract : Objective: This study aimed to compare total and regional estimates of body composition, by direct and indirect techniques, for the optimal prediction of C‐reactive protein (CRP) among young (aged 9‐12 years) Hispanic girls ( N = 232). Methods: Standard anthropometric techniques were used to measure height, weight, and waist circumference. Dual‐energy X‐ray absorptiometry (DXA) and peripheral quantitative computed tomography (pQCT) assessed body composition. Fasting serum CRP was measured by the AU5812 Clinical Chemistry Analyzer (Beckman Coulter, Brea, California). Associations between each total and regional body composition parameter and CRP were tested using linear regression (log‐transformed, continuous CRP) and ordinal logistic regression (CRP < 1.0, ≥ 1.0‐2.9, and ≥ 3.0 mg/L), controlling for maturation, dietary energy, physical activity, and medications. Results: All measures of total and regional body fat were positively associated with CRP ( P < 0.0001) except for intermuscular fat by pQCT. There were no clinically relevant differences in their association with CRP between anthropometric (BMI; waist circumference) and DXA‐derived (total fat and regional fat: trunk, gynoid, android fat, leg) measures of fat. Conclusions: Measurement of body habitus in Hispanic girls, by multiple commonly available means, predicts CRP equally well.